2020
DOI: 10.12659/msm.927727
|View full text |Cite
|
Sign up to set email alerts
|

Functional Doxorubicin-Loaded Omega-3 Unsaturated Fatty Acids Nanoparticles in Reversing Hepatocellular Carcinoma Multidrug Resistance

Abstract: Background This study investigated a nanoparticle drug delivery system to reverse multidrug resistance (MDR) and assessed its anticancer efficacy in hepatocellular carcinoma (HCC). Material/Methods Docosahexaenoic acid (DHA) was used as the functional excipient and doxorubicin (DOX) as the chemotherapeutic drug to synthesize DOX nanoparticles (DOX-nano). The human HCC cell line HepG2 was used for experiments. HepG2/DOX, HepG2+DOX, HepG2+DOX-nano, HepG2/DOX+DOX, and HepG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…As immuno-nutrients, omega-3 fatty acids are often applied in nutritional treatment of cancer [ 41 ]. They exert a crucial role in cell signaling, cell structure, and cell membrane fluidity [ 42 ]. Furthermore, they mediate the resolution of inflammation, thereby exerting an anti-inflammation effect [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As immuno-nutrients, omega-3 fatty acids are often applied in nutritional treatment of cancer [ 41 ]. They exert a crucial role in cell signaling, cell structure, and cell membrane fluidity [ 42 ]. Furthermore, they mediate the resolution of inflammation, thereby exerting an anti-inflammation effect [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that doxorubicin-loaded docosahexaenoic acid nanoparticles (DOX-nano) significantly inhibited the tumor growth [ 19 ]. HepG2/DOX cells were injected into BALB/c mice, and after that, the mice were injected with DOX-nano at 2 mg/kg for 10 days.…”
Section: Resultsmentioning
confidence: 99%
“…The authors ascribed the enhanced antineoplastic effect to several factors, such as: (i) the increased lipophilicity of the nanoformulation, which improved the drug loading efficiency; (ii) the faster DOX release rate from the omega-3 PUFA nanosystem at pH 5.0 than at pH 7.4, that may potentially decrease the secondary toxic effects of this drug; and, finally, (iii) the improved uptake of DOX when delivered to the neoplastic cells through the hydrophobic-lipid rich nanosystem. However, they did not consider the recognized and more specific antineoplastic activities of these FAs, as well as the increased efficiency shown by DOX as it was combined with a concomitant treatment with omega-3 PUFAs, as previously reported by other authors [ 37 , 46 , 61 ].…”
Section: Omega-3 Pufa-based Nanoformulations Against Bcamentioning
confidence: 99%
“…The possible antineoplastic use of omega-3 PUFAs included in nanoformulations is still attracting great attention as demonstrated by the promising results obtained over the last few years in a large array of cancers, such as hepatocarcinoma [ 46 ], neuroblastoma [ 47 ], pancreatic cancer [ 48 ] and melanoma [ 49 ] (for a review, see [ 50 ]).…”
Section: Omega-3 Pufa-based Nanoformulations Against Bcamentioning
confidence: 99%